181 Elucidating The Role Of β3-receptors In Perivascular Adipose Tissue. (31st May 2014) - Saxton, Sophie; Bussey, Charlotte; Withers, Sarah; Edwards, Gillian; Heagerty, Anthony
Abstract : Introduction: Perivascular adipose tissue (PVAT) has been shown by various studies to have an anti-contractile effect on the arteries it surrounds. The mechanism by which PVAT exerts its anti-contractile effect is not well understood, and is likely to involve the release of PVAT-derived relaxing factors (PVRF) such as adiponectin, that causes hyperpolarisation and relaxation of the vascular smooth muscle. The PVAT anti-contractile effect is lost in obesity, therefore understanding this mechanism is vital for creating novel treatments of obesity-related hypertension. We propose that the mechanism involves stimulation of adipocyte β3 -adrenoceptors in PVAT. Methods: The contractile responses of noradrenaline and serotonin were assessed in rat mesenteric small arteries using wire myography with and without PVAT, and the effects of β3 -agonist CL-316, 243 (10µM), β3 -antagonist SR59230A (1 µM), and adiponectin type-1 receptor blocking peptide were studied (2.5µM). Results: PVAT was shown to have a significant anti-contractile effect on the responses to both noradrenaline (n = 5, P = 0 .0135) and serotonin (n = 5, P = 0 .0096). The CL-316, 243 was found to have no significant effect on either the concentration-response to noradrenaline (n = 6, P = 0 .5584) or serotonin (n = 4, P = 0 .2072). SR59230A induced a significant reduction in the anti-contractility of PVAT in vessels stimulated with the highest concentration of noradrenaline (n = 3, P = 0 .0018), but not serotonin (n = 3, P = 0 0.0621). Adiponectin receptor type-1 blocking peptide has been shown to abolish the noradrenaline-induced anti-contractile effect; however in this study the blocking peptide had no significant effect on the serotonin-induced PVAT anti-contractility (n = 4, P = 0 .505). Conclusions and Implications: These results suggest that β3 -adrenoceptors may be involved in noradrenaline PVAT anti-contractility, but the serotonin-induced anti-contractile effect appears to be independent of events at β3 -adrenoceptors, and involves a different PVRF.